The credibility of transnational NGOs : when virtue is not enough - Gourevitch, Peter Alexis; Lake, David A., 1956-; Stein, Janice Gross (Cambridge : Cambridge University Press, 2012)
'We rely on NGOs to monitor the ethical practices of governments and for-profit firms and to undertake many humanitarian tasks that public and private actors will not do. While we are critical of public and private sector failures, we do not reflect enough on the credibility of the NGOs which take their place. Can we be sure that products NGOs label as child-labor free are in fact so, that the coffee labeled as'fair trade' is farmed in sustainable ways, or that the working conditions monitored by NGOs are safe and that the wages are reasonable? Can we know that humanitarian organizations are, in fact, using our donations to alleviate human suffering rather than pursuing other goals? This book explores the problems of establishing the credibility of NGO activities as they monitor working conditions, human rights and elections and provide finance through microcredit institutions, development aid and emergency assistance'--
Machine generated contents note: Introduction; 1. Beyond virtue: evaluating and enhancing the credibility of non-governmental organizations Peter A. Gourevitch and David A. Lake; Part I. Monitoring NGOs: 2. Why believe international election monitors? Susan D. Hyde; 3. Credible certification of child labor free production Irfan Nooruddin and Sarah Wilson Sokhey; 4. Becoming a household name: how human rights NGOs establish credibility through organizational structure Wendy H. Wong; Part II. Humanitarian NGOs: 5. Dilemmas of information and accountability: foreign aid donors and local development NGOs Carew Boulding; 6. In defense of virtue: credibility, legitimacy dilemmas, and the case of Islamic relief Laura Thaut, Michael Barnett and Janice Gross Stein; 7. Monitoring repayment in online peer-to-peer lending Craig McIntosh; Conclusion; 8. Credibility and compromises Peter A. Gourevitch and David A. Lake.
Includes bibliographical references and index.
Keywords: Non-governmental organizations -- Moral and ethical aspects